The impact of high nicotine concentrations on the viability and cardiac differentiation of mesenchymal stromal cells: a barrier to regenerative therapy for smokers - Gheisari, Maryam; Nosrati, Shadi; Zare, Shahrokh; Dara, Mahintaj; Zolghadri, Samaneh; Razeghian-Jahromi, Iman (Frontiers in Cell and Developmental Biology, 2024)
Background: Current treatments are not successful in restoring the lost cardiomyocytes after injury. Stem cell-based strategies have attracted much attention in this regard. Smoking, as a strong cardiovascular risk factor, not only affects the cardiac cells adversely, but also deteriorates the function of stem cells. Since mesenchymal stem cells (MSCs) are one of the popular candidates in CVD clinical trials, we investigated the impact of nicotine on regenerative properties (viability and cardiac differentiation) of these cells.Methods: MSCs were isolated from rat bone marrow, and characterized based on morphology, differentiation capability, and expression of specific mesenchymal markers. MTT assay was used to assess the viability of MSCs after being exposed to different concentrations of nicotine.Based on MTT finding and according to the concentration of nicotine in smokers' blood , growth curve and population doubling time were investigated in eight consecutive days. Cells were treated by 5-azacytidine (an inducer of cardiac differentiation), and then, expression of cardiac specific markers were calculated by qPCR.Results: MSCs were spindle-shape, capable to differentiate into adipocyte and osteocyte, and express CD73 and CD90. Viability of MSCs was reduced upon exposure to nicotine in a concentration-and time-dependent manner. Growth curve showed that nicotine reduced the proliferation of MSCs, and treated cells needed more time to be doubled. Also, expression of GATA4 and troponin were downregulated in nicotine-treated cells at day three. However, these two cardiac markers were overexpressed at day seven.Conclusions: Nicotine decreased normal growth, and reduced expression of cardiac markers in MSCs. This aspect is of eminent importance in smokers with cardiovascular disease who are candidates of stem cell therapy.